Analysis of Corporate Governance, Organisational Resilience and Sustainable Practices Developed by Brazilian Companies during the COVID-19 Pandemic: An Exploratory Study - Antony Aparecido Pavarin; Tiago F. A. C. Sigahi; Gustavo Hermínio Salati Marcondes de Moraes; Walter Leal Filho; Izabela Simon Rampasso; Rosley Anholon (World, 2022)
This paper aims to present aspects related to corporate governance, organisational resilience and sustainable practices developed by Brazilian companies during the COVID-19 pandemic. The methodological strategy included documentary research to identify sustainability reports published by companies listed on the Ibovespa index, which were examined through the content analysis technique. The results allowed light to be shed on opportunities for improvement concerning sustainability and corporate governance. Regarding organisational resilience, risk management is central for the development of sustainability practices by organisations. The support to society related to the COVID-19 pandemic was evidenced mainly through the donation of financial resources, equipment and hospital supplies. Practices related to reducing energy consumption and minimising waste generation were those most associated with environmental aspects. The actions identified were mapped according to their relations with the SDGs. Managers can benefit from the information presented in this study to enhance organisational sustainability and resilience, while researchers can use it as a starting point for future studies.